2009
DOI: 10.1152/ajprenal.90221.2008
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of SM-B, the high ATPase isoform of myosin, upregulates the PKC-mediated signal transduction pathway in murine urinary bladder smooth muscle

Abstract: Hypolite JA, Chang S, LaBelle E, Babu GJ, Periasamy M, Wein AJ, Chacko S. Deletion of SM-B, the high ATPase isoform of myosin, upregulates the PKC-mediated signal transduction pathway in murine urinary bladder smooth muscle. Am J Physiol Renal Physiol 296: F658 -F665, 2009. First published December 3, 2008 doi:10.1152/ajprenal.90221.2008.-Detrusor smooth muscle (DSM) hypertrophy induced by partial bladder outlet obstruction (PBOO) is associated with changes in the NH 2-terminal myosin heavy chain isoform from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 49 publications
1
12
1
Order By: Relevance
“…5). PKC␣ downregulation in SMB (Ϫ/Ϫ) antrum is inconsistent with the study from Hypolite et al (27) reporting PKC␣ protein expression is upregulated in detrusor smooth muscle. The difference may be tissue specific regulation of PKC␣ in SMB (Ϫ/Ϫ) mice.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…5). PKC␣ downregulation in SMB (Ϫ/Ϫ) antrum is inconsistent with the study from Hypolite et al (27) reporting PKC␣ protein expression is upregulated in detrusor smooth muscle. The difference may be tissue specific regulation of PKC␣ in SMB (Ϫ/Ϫ) mice.…”
Section: Discussioncontrasting
confidence: 61%
“…Results from Patzak et al (44) using the same animal model report that there is no correlation between SMB MHC protein expression and the rate of force generation in perfused afferent and efferent renal arterioles. Hypolite et al (27) reported that compared with the wild type the loss of SMB MHC protein in detrusor smooth muscle increases contraction force due to the upregulation of PKC-mediated signaling pathway. In spite of the studies on smooth muscle tissue function using this SMB MHC knockout mouse model, it remains unclear if and how SMA/B MHC protein expression relates to phasic and tonic muscle mechanics.…”
mentioning
confidence: 99%
“…Furthermore, PBOO in rats (13), rabbits, and patients with BPH are all associated with downregulation of BK channels (5) and increased DO, characterized by an increase in spontaneous and NVC. These studies lend further credence to the idea that BK channels play a vital role in regulating DSM excitability and thus may influence the development of spontaneous and NVC contractions under pathological conditions.PKC is an 80-kDa protein that is also involved in the regulation of smooth muscle tone and force maintenance (11,19,26). Recent evidence suggests that PKC can regulate the sensitivity of BK channels for calcium and other substrates in smooth muscle and nonmuscle cells (3,28).…”
mentioning
confidence: 99%
“…PKC is an 80-kDa protein that is also involved in the regulation of smooth muscle tone and force maintenance (11,19,26). Recent evidence suggests that PKC can regulate the sensitivity of BK channels for calcium and other substrates in smooth muscle and nonmuscle cells (3,28).…”
mentioning
confidence: 99%
“…Longitudinal muscle strips (2 by 5 mm) devoid of mucosa and serosa were obtained from wild-type (WT) and NF-B c-Rel KO mice and suspended in 7 ml of Tyrode's buffer (124.9 mM NaCl, 2.5 mM KCl, 23.8 mM NaHCO 3 , 0.5 mM MgCl 2 , 0.4 mM NaH 2 PO 4 , 1.8 mM CaCl 2 , 5.5 mM dextrose) in an organ bath (Radnoti) to equilibrate for 1 h in 95% O 2 and 5% CO 2 . The force generated in response to KCl (125 mM), electrical field stimulation (80 V, 32 Hz for 1 ms), phorbol dibutyrate (PDBu; 1 M), and carbachol (10 M) was measured using the AD Instruments PowerLab computerized system (AD Instruments) as described previously (33,34). The force measurements were normalized to the wet weight of the muscle strips.…”
mentioning
confidence: 99%